網絡學習社群專業資本積累之個案研究 Dialogue as Practice: A Case Study on the Accumulation of Professional Capital by the Networked Learning Communities - 陳佩英 Pei-Ying Chen (National Taiwan Normal University, 2017)
本研究旨在探究網絡學習社群之教學探究活動及其專業資本積累之實踐路徑與意義。履行者個案由七位臺北市立六所公立高中的國文教師組成。本研究為期2 年，資料蒐集包含深度訪談與焦點訪談、觀察紀錄、問卷與文件分析等。本研究結合網絡學習社群、專業資本與對話即實踐之概念，以之深描與詮釋該社群之發展歷程與專業資本累積之關聯。研究結果除了說明國內網絡學習社群的發展脈絡，也討論了履行者成員投入跨校社群的理由、在實踐中形塑社群主體、善用社群媒體平台打破時空限制、透過教學探究的文本生成循環而使得專業資本得以積累，以及跨校社群的網絡擴散和未來發展。社群成員因理念相通而集結，當成員參與備課－觀課－議課之時，便是創造第三空間的集體探究活動。跨校社群經由集體活動中 的言談與文本的生成循環，漸漸形成跨文本的理解，共享的優勢言談可以穿越學校城牆與教室，形成具備公共議題的敘事文本，並於教學文本的生成循環中進行探討和反思，繼而共創教育價值並賦予課程與教學新的實踐意義。 This research explored the pedagogical inquiry activities of the networked learning communities (NLCs), and the path and meaning of its professional empowerment. The case study focused on a group of teachers named the "Navigators," comprised of seven Chinese Literacy teachers from six public high schools in Taipei. This study lasted 2 years and data collection included in-depth interviews, focus group interviews, field observation, and document analysis. The concepts of NLCs, professional capital, and dialogue as practice were employed to provide thick description and a thorough interpretation of the processes and changes involved in the NLCs. The results explain the context in which the NLCs originated, the drivers of participation, how agency was developed through collaboration, the use of social media for constraint-free communication, the use of professional enquiry and reconstructed lesson texts for accumulation of professional capital, and the network expansion that led to further development of new NLCs. When participants gathered for meetings and held discussions regarding lesson plans and instructional observation, they created a "third space" for collective inquiry. Through cycles of professional dialogue and the recurrent production of lesson texts, a shared pedagogy was strengthened that guided professional discourse and enabled common understanding. This discourse was then continued within the teachers' respective schools to form a public narrative on educational practices. Along the process of recurrent production of talks and texts then practiced collaborative inquiry and reflection. This, in turn, shaped educational values and empowered the Navigators to be innovative with their curriculum and instruction.